Upaya Pengembangan Sistem Pengelolaan Keuangan Pabrik Tahu PT. TSJ Yang Bersifat Manual Menggunakan â€œAutomatic Excellent Data Validationâ€ - Yossy Dumos Herawati; Denada Oktaviani; Mawarni Dyah Nur Halaefi; Rangga Seto Hutomo; Dimas Ido Nofiyanto; Nurma Tambunan (Universitas Katolik Widya Karya Malang, 2023)
Preparation of a comprehensive budget is very important for every company, because it will provide benefits in the form of a systematic approach to management policies, as well as facilitate quantitative evaluation of the company's ultimate goals. This study aims to determine and compile a comprehensive budget calculation as a means of internal control in